Pragmatics Perspective of Genre-based Approach Essay Writing Textbook to Improve Students’ Writing Skills at English Education Department of Universitas PGRI Semarang - Dyah Nugrahani; Siti Musarokah; Theresia Cicik Sophia B. (International Journal of Research in Education, 2023)
ABSTRACT This research is aimed at developing printed teaching materials with a pragmatic perspective for college students. The design of this research is descriptive qualitative by sharing questionnaire made with google form through the WhatsApp group of two classes. The unit of analysis was the responses of 40 students from 2 classes. This research was based on a qualitative analysis of the students' responses. From the responses, it can be concluded that teaching materials have a very vital role and function in the learning process. Therefore, teaching materials should be designed and developed in such a way that they are adapted to the existing curriculum and also to the needs of students. In this research, researchers will develop an English teaching material with pragmatic perspective which are able to help English learners reach the expected communicative competence. In total, there are five sections that were asked to students. Those five sections are, 1) Textbook availability, 2) Textbook Visual, 3) Textbook Contents, 4) The Textbook Currently Being Used, and 5) Text Selections.